2021
DOI: 10.3892/or.2021.8141
|View full text |Cite
|
Sign up to set email alerts
|

Overview of serpin B9 and its roles in cancer (Review)

Abstract: Serine proteinase inhibitor B9 (serpin B9) is a member of the serine protease inhibitor superfamily, which is widely found in animals, plants and microorganisms. Serpin B9 has been reported to protect cells from the immune-killing effect of granzyme B (GrB) released by lymphocytes. In recent years, an increasing number of studies have indicated that serpin B9 is involved in tumour apoptosis, immune evasion, tumorigenesis, progression, metastasis, drug resistance and even in maintaining the stemness of cancer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 104 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…In general, Sb9 is the only intracellular ovalbumin family serpin that is expressed in certain immune cells. Moreover, it has been reported to function as a vital protector in certain cancer cells, including lung cancer, melanoma, breast cancer, and prostate cancer. ,, Besides, Sb9 is also implicated in tumor apoptosis, carcinogenesis, development, metastasis, drug resistance, and sustaining the stemness of cancer stem cells (CSCs) . Nevertheless, although Sb9 is expressed in OSCC, its role remains unclear …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, Sb9 is the only intracellular ovalbumin family serpin that is expressed in certain immune cells. Moreover, it has been reported to function as a vital protector in certain cancer cells, including lung cancer, melanoma, breast cancer, and prostate cancer. ,, Besides, Sb9 is also implicated in tumor apoptosis, carcinogenesis, development, metastasis, drug resistance, and sustaining the stemness of cancer stem cells (CSCs) . Nevertheless, although Sb9 is expressed in OSCC, its role remains unclear …”
Section: Discussionmentioning
confidence: 99%
“…9,40,41 Besides, Sb9 is also implicated in tumor apoptosis, carcinogenesis, development, metastasis, drug resistance, and sustaining the stemness of cancer stem cells (CSCs). 42 Nevertheless, although Sb9 is expressed in OSCC, its role remains unclear. 43 In this study, we observed that Sb9 is widely expressed in OSCC and may modulate the fate of cancer cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The abundance of serine in the body is also related to the occurrence of tumors. 395 For example, study found that serine upregulated in acute myeloid leukemia, 396 as well as primary melanomas. 397 Serine has recently been identified as an allosteric effect factor of M2 isoform of pyruvate kinase (PKM2).…”
Section: Metabolite Sensing and Epigenetic Regulation Of Protein Meta...mentioning
confidence: 99%
“…Resistance of tumor cells to the cytotoxic effect of cellular and humoral components of the immune system . An example is increased expression of prosurvival proteins allowing prevention of cancer cell destruction: BCL-2 [ 37 ], proteinase inhibitor 9 (PI-9, serpin B9, an inhibitor of granzyme B-mediated apoptosis) [ 38 ] and cellular FLICE inhibiting protein (c-FLIP, CFLAR) [ 39 ].…”
Section: Cancer Immunoediting Hypothesismentioning
confidence: 99%